2012
DOI: 10.1111/j.1471-4159.2012.07695.x
|View full text |Cite
|
Sign up to set email alerts
|

Cytosolic acidification and intracellular zinc release in hippocampal neurons

Abstract: In neurons exposed to glutamate, Ca2+ influx triggers intracellular Zn2+ release via an as yet unclear mechanism. Since glutamate induces a Ca2+-dependent cytosolic acidification, the present work tested the relationships among intracellular Ca2+ concentration ([Ca2+]i), intracellular pH (pHi), and [Zn2+]i. Cultured hippocampal neurons were exposed to glutamate and glycine (Glu/Gly), while [Zn2+]i, [Ca2+]i and pHi were monitored using FluoZin-3, Fura2-FF, and 2′,7′-bis-(2-carboxyethyl)-5(6)-carboxyfluorescein,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
46
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(52 citation statements)
references
References 55 publications
6
46
0
Order By: Relevance
“…The degree of pH change necessary to cause an effect on Zn 2+ handling, by contrast, significantly exceeds that reported to be caused by Baf. A pH drop below 6.7 is required to trigger an increase in intracellular Zn 2+ according to one set of studies (Kiedrowski, 2012), whereas another set has shown that metallothioneins release Zn 2+ only after cytoplasmic pH drops below 5.0 (Jiang et al, 2000). Thus, the increase in cytoplasmic Zn 2+ caused by Baf likely correlates with the loss of lysosomal function, rather than cytosolic pH changes.…”
Section: Resultsmentioning
confidence: 99%
“…The degree of pH change necessary to cause an effect on Zn 2+ handling, by contrast, significantly exceeds that reported to be caused by Baf. A pH drop below 6.7 is required to trigger an increase in intracellular Zn 2+ according to one set of studies (Kiedrowski, 2012), whereas another set has shown that metallothioneins release Zn 2+ only after cytoplasmic pH drops below 5.0 (Jiang et al, 2000). Thus, the increase in cytoplasmic Zn 2+ caused by Baf likely correlates with the loss of lysosomal function, rather than cytosolic pH changes.…”
Section: Resultsmentioning
confidence: 99%
“…4a, the cells were loaded by an application of 0.1 μM Fura-2FF AM and 0.1 μM FluoZin-3 AM for 5 min only. Earlier data showed that following such loading, the intracellular concentrations of the probes are about 1 μM (Kiedrowski 2012). Since the NEM application caused [Zn 2+ ] i elevations that saturated Fura-2FF and almost saturated FluoZin-3 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Milimolar concentration of Ca 2+ may also affect the FuraZin-1 signal (Kiedrowski 2012). This possibility was clarified in cortical neurons loaded with FuraZin-1 alone.…”
Section: Resultsmentioning
confidence: 99%
“…Of special note, FluoZin-3 is insensitive to Ca 2+ , which has a significant advantage over previous indicators that cannot differentiate between Zn 2+ and Ca 2+ signals. With the emergence of new indicators, examinations of Zn 2+ and Ca 2+ , simultaneously, using different fluorescent indicators have been reported [191, 192]. These advancements are likely to provide a better understanding of Zn 2+ regulation, conductance and functional importance.…”
Section: Prospectivementioning
confidence: 99%